EVALUASI VARIETAS PADI SAWAH PADA DISPLAY VARIETAS UNGGUL BARU (VUB) DI KABUPATEN KARAWANG, JAWA BARAT - Wage Ratna Rohaeni; M Iskandar Ishaq (Agric, 2015)
More than 80 high yielding varieties of rice have been released nationally by IAARD to support acceleration of national rice production. Inpari 13 was the one of some new variety that has been released at 2011 and have superior trait i.e early maturity and high yielding. Inpari 13 and some another new variety would disseminated at ICM program at this year. That variety needed to evaluated on Display Area and cultivated by using ICM technology and its compared with old variety as well as Ciherang. This study was to evaluate performance and yield of some new varieties compared old varieties specifically in Dem area. The experiment was conducted in West Java AIAT Dem Area, District Jayakerta, Karawang. The study was done on DS 2011 (Mei 2011-Januari 2012) by using randomized block design with 3 replications. Six varieties were tested i.e Ciherang, St. Bagendit, Inpari Inpari-7, Inpari-10, Silugunggo and Inpari-13. Integrated Crop Manajemen system i.e legowo 2:1, optimal fertilization, and IPM were used at this research. The results showed that there were signifant differences between varieties in all characters except leaf color index. Ciherang has the highest plant height (97,59 cm). Inpari-7 has the highest number of productive tillers and 100 grains weight (25 tillers/clump and 2,8 grams) and the least number of empty grains (7 grains/ panicle). St. Bagendit has the highest number of pithy grain (183 grains/panicle). Silugonggo was the early maturity but it’s resistant to stems brown planthopper (almost had a crop failure). The highest dry grain harvest was owned by Situ Bagendit (8,10 t.ha 1) followed Ciherang (8,08 t.ha-1), Inpari-13 (8,07 t.ha-1), Inpari-7 (7,52 t.ha-1), Inpari-10 (6,71 t.ha-1), and Silugonggo (2,05 t.ha-1).